Granites from Mustang and Surrounding Regions (Central Nepal) - Fort, Patrick Le; France-Lanord, Christian (Journal of Nepal Geological Society, 1995)
Two Himalayan leucogranite plutons of northern central Nepal have been recognized, mapped with the help of satellite imagery, sampled and analyzed. The 1600 km Dolpo-Mugu may be the largest High Himalaya leucogranite, and the 325 km2 Mustang leucogranite is a North Himalaya circular pluton cut in half by the Thakkhola graben. Both are very similar to the Manaslu granite. They have provided much of the filling material for the graben after a high rate of denudation.